dCROX and ROX Indices Predict Clinical Outcomes in Patients with COVID-19 Pneumonia Treated with High-Flow Nasal Cannula Oxygen Therapy - Pitchayapa Ruchiwit; Kanpisut Pongtongkam; Narongkorn Saiphoklang (Critical Care Research and Practice)
Background. High-flow nasal cannula (HFNC) therapy is a common respiratory support in patients with COVID-19 pneumonia. Predictive tools for the evaluation of successful weaning from HFNC therapy for COVID-19 pneumonia have been limited. This study aimed to develop a new predictor for weaning success from HFNC treatment in patients with COVID-19 pneumonia. Methods. We conducted a retrospective cohort study at Thammasat University Hospital, Thailand. Patients with COVID-19 pneumonia requiring HFNC therapy from April 2020 to September 2021 were included. The ROX index was defined as the ratio of oxygen saturation (SpO2)/fraction of inspired oxygen (FiO2) to respiratory rate. The CROX index was defined as the ratio of C-reactive protein (CRP) to the ROX index. dCROX was defined as the difference in CROX index between 24 hours and 72 hours. Weaning success was defined as the ability to sustain spontaneous breathing after separation from HFNC without any invasive or noninvasive ventilatory support for ≥48 hours or death. Results. A total of 106 patients (49.1% male) were included. The mean age was 62.1 ± 16.2 years. Baseline SpO2/FiO2 was 276.1 ± 124.8. The rate of HFNC weaning success within 14 days was 61.3%. The best cutoff value of the dCROX index to predict HFNC weaning success was 3.15 with 66.2% sensitivity, 70.7% specificity, and an area under the ROC curve (AUC) of 0.71 (95% CI: 0.59–0.81, p<0.001). The best cutoff value of the ROX index was 9.13, with 75.4% sensitivity, 78.0% specificity, and an AUC of 0.79 (95% CI: 0.69–0.88, p<0.001). Conclusions. ROX index has the highest accuracy for predicting successful weaning from HFNC in patients with COVID-19 pneumonia. dCROX index is the alternative tool for this setting. However, a larger prospective cohort study is needed to verify these indices for determining separation from HFNC therapy. This trial is registered with TCTR20221107004.